The E3 ligase Itch knockout mice show hyperproliferation and wound healing alteration. (12th October 2015) - Giamboi‐Miraglia, Alessandro; Cianfarani, Francesca; Cattani, Caterina; Lena, Anna Maria; Serra, Valeria; Campione, Elena; Terrinoni, Alessandro; Zambruno, Giovanna; Odorisio, Teresa; Di Daniele, Nicola; Melino, Gerry; Candi, Eleonora
Abstract : The HECT‐type E3 ubiquitin ligase Itch is absent in the non‐agouti‐lethal 18H or Itchy mice, which develop a severe immunological disease. Several of the known Itch substrates are relevant for epidermal development and homeostasis, such as p63, Notch, c‐Jun and JunB. By analysing Itchy mice before the onset of immunological alterations, we investigated the contribution of Itch in skin development and wound healing. Itchy newborn mice manifested hyperplastic epidermis, which is not present in adulthood. Itch −/− cultured keratinocytes showed overexpression of proliferating markers and increased capability to proliferate, migrate and to repair a scratch injury in vitro . These data correlated with improved in vivo wound healing in Itchy mice, at late time points of the repair process when Itch is physiologically upregulated. Despite healing acceleration, epidermal remodelling was delayed in the scars of Itch −/− mice, as indicated by enhanced epidermal thickening, keratinocyte proliferation and keratin 6 expression, and retarded keratin 14 polarization to the basal layer. Itch −/− keratinocyte prolonged activation was not associated with increased immune cell persistence in the scars. Our in vitro and in vivo results indicate that Itch plays a role in epidermal homeostasis and remodelling and this feature does not seem to depend on immunological alterations. Abstract : The HECT‐type E3 ubiquitin ligase Itch regulates keratinocyte differentiation by targeting multiple substrates (e.g. p63, c‐Jun, JunB and Notch) for protein ubiquitylation. Itch is absent in Itchy (Itch−/−) mice, which develop a severe immunological disease. Here, Candi and colleagues report that newborn Itchy mice develop epidermal hyperplasia and exhibit enhanced wound healing. Consistent with this, Itch−/− keratinocytes displayed increased capability to proliferate, migrate and to repair scratch injuries in vitro . Collectively, these data indicate that Itch plays a role in wound repair and tissue remodelling after injury.